GAMPIL FOR PUBLIC : The Application for Licensing Services - Karniawati, Nia; Purnama, Rizki Adi; Nurfatin, Nafisa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to examine about Gampil for Publict. This is an application based smartphone (Gadged) developed by the Department of Investment and Integrated Licensing Services (DPMPTSP) in Bandung City. This is government licensing services application with goal to providing ease of public services, especially licensing services. This study uses a descriptive method with a qualitative approach. The results of the study show that this application has made it easier for public to obtain licencing services. People who use this application have felt the benefits. This is in acoordance with the purpose of making this application.